Fabrication of All-Water-Based Self-Repairing Superhydrophobic Coatings Based on UV-Responsive Microcapsules - Chen, Kunlin; Zhou, Shuxue; Yang, Shu; Wu, Limin (Advanced functional materials, 2015)
Superhydrophobic coatings that are also self‐healing have drawn much attention in recent years for improved durability in practical applications. Typically, the release of the self‐healing agents is triggered by temperature and moisture change. In this study, UV‐responsive microcapsules are successfully synthesized by Pickering emulsion polymerization using titania (TiO2) and silica (SiO2) nanoparticles as the Pickering agents to fabricate all‐water‐based self‐repairing, superhydrophobic coatings. These coatings are environmentally friendly and can be readily coated on various substrates. Compared to conventional superhydrophobic coatings, these coatings can regenerate superhydrophobicity and self‐cleaning ability under UV light, mimicking the outdoor environment, after they are mechanically damaged or contaminated with organics. They can maintain the superhydrophobicity after multiple cycles of accelerated weathering tests. An environmentally benign, all‐water‐based self‐repairing superhydrophobic coating based on UV‐responsive microcapsules is fabricated, which exhibits excellent self‐healing and self‐cleaning ability in an outdoor environment, and after mechanical damage and contamination by organics.